PENGOLAHAN AIR GAMBUT DENGAN KOAGULAN CAIR HASIL EKSTRAKSI LEMPUNG ALAM DESA CENGAR MENGGUNAKAN LARUTAN H 2 SO 4 - Sutrisno, Hevi; ', Muhdarina; Amri, T. Ariful (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Liquid coagulant from Cengar clay was used for peat water treatment. The steps forproducing liquid coagulant were clay calcination at 500 o C for 3 hours and extraction by0.2 mol H 2 SO 4 solution with variation of temperature (30, 60, 100 o C) and time (1, 2, 3hours). The coagulants were tested for peat water coagulation by measuring pH,turbidity, and TDS. The results were compared to PERMENKES No.416/MENKES/PER/IX/1990 â€œTentang Syarat-syarat dan Pengawasan Kualitas Airâ€. After coagulation,the parameters of peat water were improved. The pH value of peat water aftercoagulation was between 5.0-8.5, turbidity 2.0-6.5 NTU, and TDS 250-320 mg/L.Compared to No.416/MENKES/PER/IX/1990, turbidity and TDS from all samples aftercoagulation have met the water quality standard. The best coagulant was K 100-2 with thevalue of the parameters after coagulation were 8.39 of pH, 4.75 NTU of turbidity and258 mg/L of TDS. According to the results, it can be concluded that liquid coagulantfrom Cengar clay can be used for peat water treatment.